2022
DOI: 10.3390/medicina58050584
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Periodontal Disease on Oral Health Quality of Life in Patients with Cardiovascular Disease: A Cross-Sectional Observational Single-Center Study

Abstract: Background and Objectives: Cardiovascular disease is a leading cause of global death with a rising prevalence and a heavy economic burden. Periodontal disease has been associated with cardiovascular diseases—including incident coronary heart disease, peripheral artery disease and ischemic stroke. The study evaluates the quality of life of patients with cardiovascular and periodontal disease from the point of view of oral health by using the short version of the Oral Health Impact Profile (OHIP-14) questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…CVD has always been shown to have a greater possibility of secondary oral problems. As Lazureanu et al showed in their research on the prevalence of periodontal disease in patients with CVD (44), 77.5% of the 147 patients with CVD developed periodontal disease, implying a high incidence of periodontal disease among patients with CVD. However, few related studies have explored the incidence of CVD in patients with periodontal disease.…”
Section: Discussion Major Findingsmentioning
confidence: 94%
“…CVD has always been shown to have a greater possibility of secondary oral problems. As Lazureanu et al showed in their research on the prevalence of periodontal disease in patients with CVD (44), 77.5% of the 147 patients with CVD developed periodontal disease, implying a high incidence of periodontal disease among patients with CVD. However, few related studies have explored the incidence of CVD in patients with periodontal disease.…”
Section: Discussion Major Findingsmentioning
confidence: 94%
“… 30 Another study found that in 147 patients diagnosed with CVD, 77.5% had periodontal disease and the presence of periodontal disease was also associated with a lower oral health-related quality of life. 31 A nationwide population-based cohort study reported that after a median follow-up of 9.5 years, the risk of cardiovascular events was higher when a patient had periodontal disease, a higher number of dental caries, or more tooth loss. 32 In the same study, regular dental visits, defined as once a year or more for professional cleaning, reduced cardiovascular risk by 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Right next to smoking, improper or insufficient oral hygiene is the most important and modifiable risk factor for periodontitis [ 38 , 43 ]. Insufficient oral hygiene, understood as improper or irregular tooth brushing, failure to clean interdental spaces, and avoidance of follow-up dental visits, leads to plaque accumulation [ 44 , 45 ].…”
Section: Symptoms and Risk Factors Associated With Periodontitismentioning
confidence: 99%